Judges and Juries in Civil Litigation in Later Medieval England: The Millon Thesis Reconsidered. Issue 1 (2nd January 2016) - Brand, Paul
ABSTRACT: David Millon argued in a 1989 article that medieval and early modern legal historians had been beguiled into supposing that civil litigation in these periods was decided in accordance with the 'official' legal doctrine found in law reports, plea roll arguments and Inns of Court readings when in reality their outcome was generally determined by juries exercising their own normative discretion in reaching their verdicts. This paper challenges this pessimistic conclusion, at least for the period around 1300. It demonstrates from evidence drawn from plea rolls and mainly manuscript law reports the degree of judicial control over juries exercised within the courtroom and the way in which jury verdicts were considered, and not just accepted, by courts. It also argues that the application of substantive legal rules by judges for the decision of litigation was a more important phenomenon than Millon supposed and that legal rules were also regularly invoked and applied in the preliminary pleading in cases and thereby shaped and determined the issues which went for jury decision.